Recombinant Gene Expression Reviews and Protocols - Balbás, Paulina; Lorence, Argelia (Methods in Molecular Biology, 2004)
In this updated and expanded second edition of an established classic, the editors have added critical reviews to a fresh collection of cutting-edge protocols for gene expression in bacteria, fungi, plants, plant cells, animals, and animal cells. The review articles survey new directions in recombinant gene expression research, technique, and application, and point the way to using recombinant gene expression for metabolic engineering and the production of nonprotein molecules. The readily reproducible protocols offer new host-vector systems, such as Antarctic bacteria and moderately halophytic bacteria, vectors for chromosomal editing and metabolic engineering, and information to aid in problem solving, strategy planning, and the promotion of protein folding. There are also novel heterologous gene expression schemes for cell-free systems, plant chloroplasts, microplates, hairy roots, and animal milk, and new developments in consolidated heterologous systems. The protocols follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. State-of-the-art and forward looking, Recombinant Gene Expression: Reviews and Protocols, Second Edition offers investigators seeking an overview of this critically important field not only the understanding, but also the tools needed to begin producing nonprotein products and altering the central metabolic pathways of cells to enhance heterologous gene expression